Development of a Multiple Linear Model to Forecast Cotton Yield with Reference to Weather Elements At Jalgaon - Singh, K K; Singh, R S (Annals of Arid Zone, 2016)
Multiple linear models were developed to predict the cotton yield under semi-arid conditions of Jalgaon (Maharashtra). The influence of weather factors was considered in three sub-periods corresponding to different phenological stages. Weather factors during the sub-period I (sowing to commencement of branching) alone accounted for 66.5% of the variations in the yield. These factors, when combined with the weather factors of sub-period II (branching to commencement of flowering) and sub-period III (commencement of flowering to end of flowering) accounted for about 8% of the variations in cotton yield. The low maximum temperature, lower sunshine and low humidity during germination phase are beneficial to the cotton crop. During the elongation and branching period, higher maximum temperature benefits the yield. During the flowering period higher sunshine favours the crop yield.